Uji Efektifitas Ekstrak Daun Sirih Merah sebagai Anti Hiperglikemia pada Tikus Putih Diinduksi Aloksan - Try Susanti; Dwi Gusfarenie; Nining Nuraida (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Diabetes melitus or diabetes is a health disorder in the form of a collection of symptoms that arise in a person caused by increased blood sugar leves due to insulin deficiency or insulin resistance and metabolic disorders in general. Red bete leaves contain chemical compounds of alkaloids, flavonoids, tannins and saponins which can lower blood sugar leves. The aim of this study was to determine the effectiveness of red bete leaf extract suspension (Piper crocatum) as antihyperglycemia in male white rats (Rattus novergicus) induced by alloxan. This research method is experimental. The extraction process for red bete leaves uses 70% ethanol solvent using the maceration method, then concentrated using a rotary evaporator and thickened using a water bath, then a suspension preparation is made, the doses given to male white rats are 2%, 4% and 6%. Glibenclamide suspension as a positive control and suspending agent as a negative control. The effectiveness of the red bete leaf extract suspension was seen from the reduction in blood sugar leves in mice after being induced by alloxan. The research data were analyzed using One Way ANOVA and paired sample t-test. The resuts of the study showed that red bete leaf extract suspension was effective as an antihyperglycemia, where the most effective dose was 6%. The suspension preparation of red bete leaf extract meets the requirements for evaluation of the preparation and stability of the preparation.